Emergency medical services responders' perceptions of the effect of stress and anxiety on patient safety in the out-of-hospital emergency care of children: a qualitative study. Issue 2 (28th February 2017) - Guise, Jeanne-Marie; Hansen, Matthew; O'Brien, Kerth; Dickinson, Caitlin; Meckler, Garth; Engle, Phil; Lambert, William; Jui, Jonathan
Abstract : Objective: Prehospital emergency medical services (EMS) providers report anxiety as the second most common contributor to paediatric patient safety events. The objective of this study was to understand how EMS providers perceive the effect of stress and anxiety on paediatric out-of-hospital patient safety. Setting: This was a nationwide study of EMS providers from 44 of 50 (88%) US states. Participants: A total of 753 eligible EMS professionals, including emergency medical technicians, emergency department physicians and nurses (general and paediatric), and respiratory therapists who participate in out-of-hospital transports. Primary and secondary outcome measures: Outcomes included responses to: (1) clinical situations where heightened stress or anxiety was likely to contribute to safety events, (2) aspects of these clinical situations that cause stress or anxiety and (3) how stress or anxiety may lead to paediatric safety events. Results: EMS providers reported that the clinical situations where stress and anxiety were more likely to contribute to paediatric patient safety events were trauma, respiratory distress and cardiac issues. Key themes were: (1) provider sympathy or identification with children, (2) difficulty seeing an innocent child hurt and the inherent value of children and (3) insufficient exposure to paediatric emergencies. Conclusions: Caring for paediatric emergencies creates unique stresses on providers that may affect patient safety. Many of the factors reported to cause provider stress and anxiety are inherent attributes of children and therefore not modifiable. Tools that support care during stressful conditions such as cognitive aids may help to mitigate anxiety in the prehospital care of children. Further research is needed to identify opportunities for and attributes of interventions.